Extradural Spinal Compression - O. H. Sorour; I. El - Shafey; Khairy Samra (Acta Medica Iranica, 1964)
100 cases of extradural spinal compression comprising 74% of all cases of spinal  compression were included. Ver-tebral and extravertebral compression occurred with  equal frequency.